Evaluation of milk production in murrah buffalo cows under different farm management system - Zainuddin, Nur Syahirah (2017)
This aim of this study is to compare the milk yield of buffalo cows kept under good management (GM) practice and poor management (PM) practice. The management of the farm were assessed according to standard management guidelines for efficient dairy buffalo production (Thomas, 2008). A number of five (5) ‘Ladang Angkat’ Universiti Putra Malaysia farms were selected: GM farms were located in Mukim Ulu Melaka, Langkawi and Sungai Tangkas, Kajang whereas the PM farms were in Kuah Langkawi, Taman Sri Jelok Kajang and Sungai Batangsi Semenyih. A total number of 30 and 49 animals were selected from PM and GM farms respectively and the milk yield for the entire farm were recorded for 3 to 5 days consecutively. Past records data of up to 3 months (since November 2016) were also taken from every farm to evaluate the consistency of milk yield. Farmers were interviewed for farm information on reproductive performance and health problems. Clinical mastitis was assessed based on udder and milk abnormalities. The results revealed that the average daily milk yield of cows from GM farm was 6.319 litres (standard deviation, SD=1.2) and cows from PM farm was 4.421 litres (SD=2.4), of which the difference average milk yield was statistically significant (t value=7.908,df=229,p<0.05). The identified clinical reproductive problems for both farms were similar (p>0.05). This study generally suggests that buffalo cows in GM farm may perform better compared to cows from PM farm.